Impact of Cultural Indicators on the Economic Performance of International Companies - Kuprina, Tamara V.; Ivanova, Galina O. (Economy of Regions, 2021)
Nowadays, international companies are looking for new ways to improve their performance. Most studies on this issue do not consider the social environment and established corporate culture that have a direct impact on economic indicators. Based on econometric data, this research confirms the impact of cultural indicators on the economic activities of international companies in Russia, Germany and Japan, representing national, European and Asian cultures. Th quantitative Denison’s method allowed us to examine the corporate culture and assign numerical values to its characteristics. The impact of cultural indicators (engagement, consistency, adaptability, mission) was assessed by means of correlation and regression analysis. According to the data obtained, even though employee engagement is shown to be the most important indicator in general, the performance and economic indicators of various enterprises are affected differently. For Russian companies, the most significant cultural indicators determining the overall performance are adaptability and engagement, as the mission indicator has the least impact. We factors of mission and engagement are of utmost importance for German organisations, while consistency and adaptability are less relevant. We economic performance in Japanese companies is strongly influenced by their mission and consistency, and the indicators of engagement and adaptability are secondary. However, the conducted research does not cover the whole variety of interactions between international companies. Future interdisciplinary studies should examine how cultural indicators influence the economic activity of companies of countries in different world regions. In the context of globalisation and localisation processes, international companies need to adapt their activities, taking into account the local cultural values.